“Implementación de un sistema electrónico para el control de calidad de huevos de gallina mediante procesamiento de imágenes” - Tapia Carrera, Mauricio Efraín (2024)
This thesis presents the prototype of an electronic system for quality control of chicken eggs, using artificial intelligence through image processing, it was carried out with the free programming Python language software. The model is made up of a laser-cut MDF wooden structure and a 3D printed conveyor belt, which has a Nema 17 stepper motor, an Mg995 servo motor, a 120 Vac - 12Vdc source, voltage distribution board, arduino 1, 4988 drivers, they are programmed in free Arduino software; Inside it is the high-speed VGA 100fps Full HD 1080P USB webcam for image processing and a 50-Watt LED panel for lighting. The images are processed by applying Gaussian filter to blur image noise, then RGB Thresholding is applied to BGR. The percentage error for the area size is analyzed in a general way, where the estimation of the product area and the efficiency of the algorithm is 98.19%, which shows that the algorithm fails the estimation by 1.81%, which is close to the real value. The analysis results are saved in a database. Finally, the 15 egg samples are sorted to be introduced into the automatic classification module which will give us the area values of the object (chicken egg) located in the test area.